Pengaruh Perputaran Modal Kerja, Likuiditas, Leverage dan Aktivitas Terhadap Profitabilitas Sub Sektor Ritel yang Terdaftar di Bursa Efek Indonesia - Sispa Dasilpa; Masdar Mas’ud; Arifin Arifin (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Abstract This study aims to determine the effect of working capital turnover, liquidity, leverage, and activity on the profitability of the retail sub-sector listed on the Indonesia Stock Exchange. This study employed quantitative research. The population comprised 32 companies, with a sample size of 19 retail companies. Purposive sampling was used for the sampling. SPSS was used for the testing. Data analysis employed multiple linear regression, coefficient of determination, simultaneous analysis, and hypothesis testing. The results of this study indicate that working capital turnover (Receivable Turnover) does not significantly affect (ROE) in retail sub-sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Liquidity (Quick Ratio) does not significantly affect profitability (ROE) in retail sub-sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Leverage (DAR) does not significantly affect profitability (ROE) in retail sub- sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Activity (FAT) has a negative and significant effect on profitability (ROE) in retail sub-sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Simultaneously, Receivable Turnover, Quick Ratio (QR), Debt To Asset Ratio (DAR), and Fixed Asset Turnover (FAT) simultaneously have a significant effect on Return on Equity (ROE) in retail sub-sector companies listed on the Indonesian Stock Exchange for the 2022-2024 period. Keywords: Working Capital Turnover, Liquidity, Leverage, Activity, Profitability, Retail Companies.